Optimization of Xanthorrhizol Nanoemulsion Formulation Using The Design of Experiment Approach (Box-Behnken Methods) - Naiya Salsabila Az-zahra; Uswatul Hasanah; Rahmi Nofita (JSFK (Jurnal Sains Farmasi & Klinis), 2025)
Nanoemulsion is an effective drug delivery system to enhance the penetration of active substances. Xanthorrhizol (XNT) shows potential as an anti-aging agent with collagenesis activity and photo-aging inhibition, but its lipophilic nature limits skin penetration and reduces its effectiveness in reaching the stratum corneum. Therefore, this study aims to optimize the formulation of xanthorrhizol nanoemulsion using the Design of Experiment (DoE) statistical approach with the Box-Behnken Design (BBD) method on the Design Expert® software. The optimization in this study involved three independent variables (X): (X₁) the concentration of Smix (Tween 80 and PEG 400), (X₂) stirring time, and (X₃) stirring speed. The responses (Y) evaluated to determine the optimization outcome were (Y₁) percent transmittance (%T) and (Y₂) pH. Based on the optimization results, the base formula with the amount of Smix 60%, stirring speed 875 rpm and stirring time 15 minutes gave a 98.4%T response and pH 7.05. The xanthorrhizol nanoemulsion formula was yellow in color and had a distinctive xanthorrhizol odor. The formulation exhibited a globule size of 13.76 ± 0.2 nm, a polydispersity index of 0.059 ± 0.000, and a zeta potential of −48.03 ± 1.423 mV. It also showed 95.5 ± 0.31% transmittance, had a pH of 7.12 ± 0.01, and was classified as an oil-in-water (O/W) nanoemulsion. The nanoemulsion remained stable after freeze-thaw and centrifugation tests, with an entrapment efficiency of 58.6%. Based on these findings, the developed formulation can be considered a promising nanoemulsion system for xanthorrhizol delivery